2014
DOI: 10.1213/ane.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Reduces Mechanical Hyperalgesia and Glial Cell Activation in Animals with Neuropathic Pain

Abstract: Spinal cord stimulation (SCS) is used to manage chronic intractable neuropathic pain. We examined parameters of SCS in rats with spared nerve injury by modulating frequency (4Hz vs. 60Hz), duration (30m vs. 6h), or intensity (50%, 75%, or 90% MT). To elucidate potential mechanisms modulated by SCS, we examined immunoreactivity glial markers in the spinal cord after SCS). An epidural SCS lead was implanted in the upper lumbar spinal cord. Animals were tested for mechanical withdrawal threshold (MWT) of the paw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 97 publications
7
111
1
Order By: Relevance
“…Nevertheless, clinically, these results are indicative of an effective treatment. The behavioral results are consistent with previous studies, 12,13 done under different stimulation conditions, allowing us to draw connections between genetic changes and behavioral responses regarding injury status and SCS-induced analgesia.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, clinically, these results are indicative of an effective treatment. The behavioral results are consistent with previous studies, 12,13 done under different stimulation conditions, allowing us to draw connections between genetic changes and behavioral responses regarding injury status and SCS-induced analgesia.…”
Section: Discussionsupporting
confidence: 89%
“…This is the first study to show the long-term effectiveness of SCS with repeated treatment and to show improvements in physical activity. Prior studies have shown that a single treatment or treatment for 4 -5 days reduces mechanical hyperalgesia of the paw after nerve injury in multiple models (Guan et al, 2010;Maeda et al, 2009;Smits et al, 2006;Song, Ansah, Meyerson, Pertovaara, & Linderoth, 2013;Truin et al, 2011;Sato et al, 2013;Sato et al, 2014). The magnitude of the reduction varies considerably between studies, with some reports showing nearly complete reversal and others showing a smaller reversal.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that 4 days of SCS, both 4 and 60 Hz, reduces SNI-induced glial cell activation (Sato et al, 2014). SCS has been used for more than 30 years to treat chronic pain, particularly neuropathic pain (Gybels & Sweet, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 These include central mechanisms of cortical reorganization, 57-59 inhibition of neural conduction at the dorsal horn and supraspinal structures, 56,[60][61][62][63] GABAergic and endogenous opioid receptor activation, 61,64,65 attenuation of wide dynamic range neuronal excitability and decreased glial cell activation, 66,67 and sympathetic nervous system inactivation with resultant improvements in peripheral circulation. 68,69 Successful treatment with SCS is more than a dichotomous "yes" or "no" assessment for pain or the attainment of an arbitrary 50% analgesia.…”
Section: Discussionmentioning
confidence: 99%